2013
DOI: 10.5491/shaw.2013.4.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Occupational Injuries in Korea from 2001 to 2010

Abstract: ObjectivesThis study is planned to assess the trend of occupational injuries in Korea from 2001 to 2010.MethodsTen years of occupational injuries, from 2001 to 2010, were analyzed in order to investigate the changing profiles according to the various characteristics of injuries; economic sectors, age of the injured, and type of injuries. The changing profile of occupational injuries was investigated by comparison with an index-created relative value based on the number of cases of reference category.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…This is believed to be the first national level comparison of occupational injuries/diseases between SIWs and NSI-Ws. The index value calculation method has already been used in different studies conducted in Turkey, Republic of Korea and Pakistan to determine trends in occupational injuries (9,11,12). Overall, this study found a clear higher percentage share of NSIW with SIW by employment (4 times) and occupational injuries/diseases (14 times).…”
Section: Discussionmentioning
confidence: 69%
“…This is believed to be the first national level comparison of occupational injuries/diseases between SIWs and NSI-Ws. The index value calculation method has already been used in different studies conducted in Turkey, Republic of Korea and Pakistan to determine trends in occupational injuries (9,11,12). Overall, this study found a clear higher percentage share of NSIW with SIW by employment (4 times) and occupational injuries/diseases (14 times).…”
Section: Discussionmentioning
confidence: 69%
“…Ozden et al (2011) [2] state that all countries that provide incidence rate statistics by industry report the highest rates in forestry. Regardless of the use of modern techniques and machinery, occupational accidents are frequent and, in many cases, fatal, especially in forest harvesting [3,4]. These accidents are often followed by material and environmental damage, as well as financial compensations to the victims or their families [5], thus having additional effects on the financial stability of businesses in forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies in China have shown that 43.6–79.3% of hand injuries requiring emergency medicine are work‐related acute hand injuries [Wang et al, ; Ye et al, ; Li and Wang ; Fitzgerald et al, ]. Descriptive studies have shown that occupational hand injuries occur mainly in manufacturing industries [Rhee et al, ]. A study in China found that 85.4% of occupational hand injury cases involved manufacturing workers, and 59.5% were associated with power machines [Jin et al, ].…”
Section: Introductionmentioning
confidence: 99%